Auxospore wall structure and postsexual valve morphology in Rhabdonema minutum Kützing - Irena Kaczmarska; James M. Ehrman (Plant and Fungal Systematics, 2019)
Several decades ago, three members of the araphid pennate genus Rhabdonema (R. adriaticum, R. arcuatum, R. minutum) were the first araphid diatoms studied using cultures and electron microscopical methods to determine auxospore structure and development. Of these, R. minutum was the least documented at that time. None have been reinvestigated until now. Here we present the structural elements of the mature auxospore and the initial and postsexual valve characteristics of R. minutum. Although in general the auxospore wall of this diatom is similar to that of the two other species examined (to the extent that they were documented), there are intriguing differences. Most unanticipated is the structure of the primary band of the longitudinal perizonium, which shows remarkable similarities to the raphid pennate diatom valve. The evolutionary implications of such a similarity are considered.